2017
DOI: 10.1002/elps.201600436
|View full text |Cite
|
Sign up to set email alerts
|

AC dielectrophoretic manipulation and electroporation of vaccinia virus using carbon nanoelectrode arrays

Abstract: This paper reports the capture and detection of vaccinia virus particles based on AC dielectrophoresis (DEP) and electrochemical impedance measurements employing an embedded vertically aligned carbon nanofiber (VACNF) nanoelectrode array (NEA) versus a macroscopic indium-tin-oxide (ITO) transparent electrode in a "points-and-lid" configuration. The nano-DEP device was fabricated by bonding two SU-8 covered electrodes patterned using photolithography. The bottom electrode contains a 200 × 200 μm active region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Going even further, the development of nontraditional materials has allowed scientists to examine viruses in a new way, as is seen in the work of Madiyar et al. [40]. The basis of manipulation is with AC DEP, but the arrays are made of carbon nanofibers creating a nanoelectrode array [40].…”
Section: Analyzing and Sensing Of Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Going even further, the development of nontraditional materials has allowed scientists to examine viruses in a new way, as is seen in the work of Madiyar et al. [40]. The basis of manipulation is with AC DEP, but the arrays are made of carbon nanofibers creating a nanoelectrode array [40].…”
Section: Analyzing and Sensing Of Virusesmentioning
confidence: 99%
“…[40]. The basis of manipulation is with AC DEP, but the arrays are made of carbon nanofibers creating a nanoelectrode array [40]. The design and material allowed for the capture of viral particles at a lower AC voltage of 8.0 V with a 1.0 kHz frequency; additionally, the group reported that at 50 Hz or less, electroporation can occur due to the electric field at the carbon nanofiber tips [40].…”
Section: Analyzing and Sensing Of Virusesmentioning
confidence: 99%
“…The application of DEP to the biomedical field has recently gained significant attention. DEP can be used in several areas including cancer disease diagnostics [36], stem cell‐based therapy [32,42], and diagnosis of infectious diseases [30,43,44]. In this review, the recent applications of DEP to the biomedical field are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al created a sensor for influenza virus employing carbon nanotubes that were electrodeposited by means of DEP [27]. Madiyar et al reported the capture and detection of vaccinia virus with DEP by using carbon nanoelectrode arrays [28]. Some earlier studies involved plant viruses.…”
Section: Introductionmentioning
confidence: 99%